2014
DOI: 10.1007/s10815-013-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Embryo quality but not pronuclear score is associated with clinical pregnancy following IVF

Abstract: Purpose The association between pronuclear (PN) scoring of embryos from assisted reproductive technology (ART) and clinical pregnancy remains controversial. We hypothesized that embryos with PNs scored on the day of fertilization check offer better embryo selection on day 3 and higher CPR compared to non-PN scored embryos. Methods Patients (19-46 years) undergoing IVF/ICSI cycles at Montefiore's Institute for Reproductive Medicine and Health between January 2006 and December 2009 were included in our study. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Hormonal and secreted factors produced by both the embryo and the endometrium (41,45,75,7981), morphological differences (8290) and genetic and epigenetic alterations not detected by PGS all potentially represent implantation and survival barriers. A more comprehensive understanding of these barriers is not likely be addressed by additional clinical studies of EnT or EnP alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal and secreted factors produced by both the embryo and the endometrium (41,45,75,7981), morphological differences (8290) and genetic and epigenetic alterations not detected by PGS all potentially represent implantation and survival barriers. A more comprehensive understanding of these barriers is not likely be addressed by additional clinical studies of EnT or EnP alone.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant hCG (250 μg sc., Ovitrelle, Serono, Istanbul, Turkey) was administered when at least three follicles showed a mean diameter of 18 mm, and oocyte retrieval was done 36 h after the hCG injection by the guidance of transvaginal ultrasonography, and ICSI was used for all IVF-ET patients. Fresh single-embryo transfers performed on day 3 to all women [14]. Luteal support was given by vaginal progesterone (Crinone 8 % gel, Serono, Istanbul), and supplementation was started on hCG administration day [15].…”
Section: In Vitro Fertilization Stimulationmentioning
confidence: 99%
“…Few authors researched the relation between PCOS and serum AA protein documenting different results with increased serum levels in PCOS [2,12,13] or no difference with the controls [1]. Up to our knowledge, there is only one report in the literature studying the levels of AA protein in follicular fluid (FF) of women undergoing controlled ovarian stimulation for in vitro fertilization [14]. Therefore in this study, we aimed to investigate serum and follicular fluid levels of AA protein in nonhyperandrogenic, non-obese patients with PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different evaluated parameters, pronuclei (PN) scoring has been a subject of debate. Although some studies have shown a prognostic effect of PN scoring, one study concluded that further refinement of embryo grading by PN scoring is not beneficial . Over the last decade, an ET at the blastocyst stage has been used more frequently to select the best embryo and to decrease the number of transferred embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown a prognostic effect of PN scoring, 5,6 one study concluded that further refinement of embryo grading by PN scoring is not beneficial. 7 Over the last decade, an ET at the blastocyst stage has been used more frequently to select the best embryo and to decrease the number of transferred embryos. However, the transfer of embryos at the blastocyst stage is occasionally avoided and they are transferred at an earlier stage, especially when patients have few embryos or when embryos might not tolerate expanded culture conditions.…”
mentioning
confidence: 99%